Thiamin and Riboflavin in Human Milk: Effects of Lipid-Based Nutrient Supplementation and Stage of Lactation on Vitamer Secretion and Contributions to Total Vitamin Content. - Daniela Hampel; Setareh Shahab-Ferdows; Linda S Adair; Margaret E Bentley; Valerie L Flax; Denise J Jamieson; Sascha R Ellington; Gerald Tegha; Charles S Chasela; Debbie Kamwendo; Lindsay H Allen (PLoS ONE)
While thiamin and riboflavin in breast milk have been analyzed for over 50 years, less attention has been given to the different forms of each vitamin. Thiamin-monophosphate (TMP) and free thiamin contribute to total thiamin content; flavin adenine-dinucleotide (FAD) and free riboflavin are the main contributors to total riboflavin. We analyzed milk collected at 2 (n = 258) or 6 (n = 104), and 24 weeks (n = 362) from HIV-infected Malawian mothers within the Breastfeeding, Antiretrovirals and Nutrition (BAN) study, randomly assigned at delivery to lipid-based nutrient supplements (LNS) or a control group, to investigate each vitamer's contribution to total milk vitamin content and the effects of supplementation on the different thiamin and riboflavin vitamers at early and later stages of lactation, and obtain insight into the transport and distribution of these vitamers in human milk. Thiamin vitamers were derivatized into thiochrome-esters and analyzed by high-performance liquid-chromatography-fluorescence-detection (HPLC-FLD). Riboflavin and FAD were analyzed by ultra-performance liquid-chromatography-tandem-mass-spectrometry (ULPC-MS/MS). Thiamin-pyrophosphate (TPP), identified here for the first time in breast milk, contributed 1.9-4.5% to total thiamin. Free thiamin increased significantly from 2/6 to 24 weeks regardless of treatment indicating an active transport of this vitamer in milk. LNS significantly increased TMP and free thiamin only at 2 weeks compared to the control: median 170 versus 151 μg/L (TMP), 13.3 versus 10.5 μg/L (free thiamin, p<0.05 for both, suggesting an up-regulated active mechanism for TMP and free thiamin accumulation at early stages of lactation. Free riboflavin was consistently and significantly increased with LNS (range: 14.8-19.6 μg/L (LNS) versus 5.0-7.4 μg/L (control), p<0.001), shifting FAD:riboflavin relative amounts from 92-94:6-8% to 85:15%, indicating a preferred secretion of the free form into breast milk. The continuous presence of FAD in breast milk suggests an active transport and secretion system for this vitamer or possibly formation of this co-enymatic form in the mammary gland.